The art and science of mindfulness : integrating mindfulness into psychology and the helping professions - Shapiro, Shauna L.; Carlson, Linda E. (American Psychological Association, 2017)
"Intention is fundamental to any project, endeavor, or journey. Related to intention is the concept of mindfulness--the awareness that arises through intentionally attending to oneself and others in an open, caring, and nonjudgmental way. Authors Shapiro and Carlson draw from Eastern wisdom and practices as well as Western psychological theory and science to explore why mindful awareness is integral to the therapeutic healing process and to show clinicians how to connect with this deeper awareness. This second edition is an accessible discussion of the fundamentals and also contains new sections describing the latest research on the neuroscience of mindfulness and mechanisms of change. Integrating the art and science of mindfulness to inspire greater well-being in both clinicians and their patients, this volume bridges a gap between therapist and patient, reminding us that we are all human beings wanting health, happiness, and freedom from suffering"--Publicity materials. (PsycINFO Database Record (c) 2017 APA, all rights reserved).